Pengembangan Badan Usaha Milik Desa (BumDes) Untuk Kesejahteraan Ekonomi Masyarakat Desa Bukit Ranah Kabupaten Kampar Provinsi Riau - Kiki Joesyiana; Asepma Hygi Prihastuti; Sri Wahyuni; Desi Susanti (Jurnal Pengabdian Masyarakat Madani, 2021)
This service aims to provide knowledge to the residents of the hill realm village, especially members of the Bukit realm Village Owned Enterprise so that they can maximize the benefits of the existence of the BUMdes that they have and are able to manage and develop the BUMdes in order to help provide initial business capital to cooperative members, namely the residents of the hill village. realm, so that in the future many hill village residents can enter the business world and for those who already have a business, can take advantage of the existence of BUMdes that they have to advance and develop their business. Village-Owned Enterprises are village businesses that are managed by the village government and are legal entities. The village government can establish village-owned enterprises of the same age as the needs and potentials of each village. The formation of village-owned enterprises is determined by village regulations. The management of village-owned enterprises consists of the village government and the local community. The capital of village-owned enterprises can come from the village government, community savings, government assistance, provincial governments and district/city governments, loans, or other party's capital participation or profit-sharing cooperation on the basis of mutual benefit. Village-owned enterprises can make loans, which can be done after obtaining BPD approval. Until now, most BUMDes are still standing and do not have productive business activities due to various problems that have prevented BUMdes from growing as expected. In Bukit Ranah Village there is a Village-Owned Business Entity which is a legal entity whose members are residents of the hill realm village itself.